Be sensei, my friend: Aikido training with a remotely controlled proxy trainer - Suzuki, Takashige; Uhde, Alarith; Nakamura, Takuto; Narumi, Takuji; Amemiya, Tomohiro; Kuzuoka, Hideaki (Frontiers in Virtual Reality, 2024)
Contact sports such as Aikido are preferred to be trained in person with an experienced trainer, as the attempts of remote training before and during the COVID-19 pandemic failed to reproduce the quality of the in-person training benefiting from the trainer's physically present body. To address this issue of replicating in-person experience remotely, we proposed "Sensei possession", an xReality-based training method for contact sports in which the trainer remotely guides a person who performs the physical interaction with the trainee on behalf of the real trainer in real-time. In this study, to test the effectiveness of "Sensei possession" on training performance and examine the concerns about its possible side effects on motivation, we conducted a between-participants experiment with an Aikido training task[N = 10 pairs(20 people)]. We compared the groups with or without live feedback on the proxy trainers under our hypothesis that live feedback would enhance trainees' performance gain. As a result, the trainees in the group with live feedback on proxy trainers had more performance gain than those without live feedback, and no indication of negative effects on motivation was shown. We discussed our results concerning the previous research on micro-adaptive training and reported technical insights to improve the design of Sensei possession further.